Diagnostic Challenges of Benign Fibro-Osseous Lesions and Psammomatous Meningiomas of the Craniofacial Region: A Comparative Review of their Clinico-pathological Features - Nwizu, BDS, MMSc, Ngozi N.; Aguirre, DDS, MS, Alfredo; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2010)
Conventional ossifying fibroma (COF), juvenile psammomatoid ossifying fibroma (JPOF), juvenile trabecular ossifying fibroma (JTOF), fibrous dysplasia (FD), cemento-osseous dysplasia (COD) and psammomatous meningioma (PM) share overlapping clinico-pathologic characteristics. This can be diagnostically challenging for pathologists. Although remarkable progress has been made over the years using ancillary studies like immunohistochemistry and molecular cytogenetics to distinguish histologically similar diseases; such diagnostic aids are yet to be successfully employed within this group of lesions. The implication is that pathologists have to rely heavily on traditional H&E stained sections in differentiating these lesions. It is important to make the distinction because of differences in their clinical behavior, modes of treatment and prognosis. In this article, the clinico-pathologic features of each entity are reviewed.